(untitled) (Thobaqot: Jurnal Ilmu Hadis, 2023)
Marriage in Islam is a contract that permits intercourse between men and women who are not mahram. Among the things that are always discussed and debated regarding marriage in Islam are matters relating to monogamy and polygamy. The widespread behavior of husbands who choose monogamy but behind their backs their wife has an affair (another dream woman) outside of marriage is currently causing concern, so in this case it is necessary to carry out further research regarding monogamy which was carried out during the time of the Prophet Muhammad. This research was conducted to find out how Fazlur Rahman’s hermeneutical theory is applied to the hadith narrated by al-Bukhari index number 4829 regarding monogamy. In this research, the type of research used by researchers is library research. As for this research, it can be concluded that in understanding the monogamy hadith in al-Bukhari’s history index number 4829, one can conclude that the moral purpose contained in this hadith is that these legal provisions do not apply to Ali bin Abi Talib only but rather apply to Muslims. It is prohibited to harm anyone who causes the Prophet SAW to feel hurt, because hurting the Prophet SAW is haram according to the agreement. Then, if polygamy brings jealousy to a woman, then the woman has the right to receive protection from her guardian and her guardian must try to be the main shield for her daughter as an effort to defend her daughter.